2005
DOI: 10.1515/cclm.2005.165
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and analytical performance of a screening panel for allergy

Abstract: Worldwide, allergic diseases are increasing in prevalence and incidence. Early assessment of the immunoglobulin E (IgE) sensitisation status has a major impact on clinical outcome and selection of therapeutic options. Recently, a number of new IgE-detecting test systems have entered the market, including screening tests allowing identification of a wide spectrum of sensitising allergens. We evaluated the analytical and diagnostic performance of the newly developed Allergy Screen test panel for atopy (Mediwiss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 13 publications
1
34
0
Order By: Relevance
“…However, Herzum et al [10] found that the Allergy Screen panel yields reliable results in the detection of allergic sensitization to common allergens.…”
Section: Discussionmentioning
confidence: 99%
“…However, Herzum et al [10] found that the Allergy Screen panel yields reliable results in the detection of allergic sensitization to common allergens.…”
Section: Discussionmentioning
confidence: 99%
“…Venous blood samples collected from children at the ages of 1 and 6 years, and from mothers and fathers, were analyzed for allergen-specific immunoglobulin E (IgE) to 19 common allergens (Mediwiss Analytic, Moers, Germany) 14 ; 13 inhalant and 6 food allergens were included. 10 The cutoff level to define atopic sensitization to inhalant allergens was 0.70 kU/L at the age of 6 years, and this factor was analyzed in 310 children with data on home inspection in infancy.…”
Section: Immunoglobulin E Determinationsmentioning
confidence: 99%
“…This method has previously been validated against the in vitro IgE CAP system (Pharmacia, Freiburg, Germany) and the skin prick test. 12 Food allergens included hen's egg, cow's milk, peanut, hazelnut, carrot, wheat flour, and soybean; inhalant allergens comprised Dermatophagoides pteronyssinus, Dermatophagoides farinae, cat, horse, dog, Alternaria species, mugwort, plantain, alder, birch pollen, hazel pollen, rye pollen, and a grass pollen mix. In addition, peripheral blood samples of the mothers were taken at birth (in Switzerland and Finland) or at a home visit when the child was 2 months old and were assessed for IgE levels.…”
Section: Specific Ige In Serum Samplesmentioning
confidence: 99%